2020
DOI: 10.1039/d0ce00366b
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput on demand access of single enantiomers by a continuous flow crystallization process

Abstract: A novel continuous flow reactive crystallization process for the in situ on-demand access of single enantiomer crystals is reported and exemplified for a chiral pharmaceutical intermediate that crystallizes as a racemic conglomerate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…22 Over the last two decades, the continuous mode has gained the interest of industry and academia due to its many advantages 23 over discontinuous mode including better reproducibility and yields, 49,[51][52][53] shorter development period and costs, 30 smaller equipment footprint 55 (up to 20% reduction in the CapEx) 23 and precise control of process parameters. 54 There are some challenges found in literature associated with the scale-up of continuous crystallization including fouling, clogging, and encrustation. Such events are predominantly caused by heterogeneous nucleation due to insufficient heat transfer or equipment material differences between scales.…”
Section: Preferential Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Over the last two decades, the continuous mode has gained the interest of industry and academia due to its many advantages 23 over discontinuous mode including better reproducibility and yields, 49,[51][52][53] shorter development period and costs, 30 smaller equipment footprint 55 (up to 20% reduction in the CapEx) 23 and precise control of process parameters. 54 There are some challenges found in literature associated with the scale-up of continuous crystallization including fouling, clogging, and encrustation. Such events are predominantly caused by heterogeneous nucleation due to insufficient heat transfer or equipment material differences between scales.…”
Section: Preferential Crystallizationmentioning
confidence: 99%
“…7). 91 Recently, Cameli et al 54 reported the continuous preferential crystallization of isoindoline-1-ones derivatives using a plug flow crystallizer immersed in two thermostatic baths set at different temperatures. This configuration allowed them to obtain productivities of 20 g L −1 h −1 due to the excellent heat transfer and low residence periods (Table 4 and Fig.…”
Section: Preferential Crystallizationmentioning
confidence: 99%
“… 24 Another step toward industrial application is based on the batch temperature cycling experiments carried out in a microwave reactor, 25 i.e., exploiting very fast heating and cooling rates, and its continuous alternative was presented by employing spatial thermal oscillations in a tubular flow millireactor. 26 In a recent work, the feasibility of performing continuous temperature cycles in a continuous tubular crystallizer was demonstrated. 27 Nevertheless, to the best of our knowledge, application of periodic temperature cycles in mixed suspension mixed product removal crystallizers (MSMPRCs) for the purpose of solid-state deracemization has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of crystal growth, dissolution, and agglomeration kinetics provided here can be readily combined with previously existing breakage/secondary nucleation models 14,20,21 for sodium chlorate to quantitatively simulate complex crystallization processes such as deracemization through Viedma ripening or temperature cycling. 18,22 2. THEORY 2.1.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the dissolution rates of sodium chlorate are estimated under operating conditions similar to the ones used for the growth experiments. The quantification of crystal growth, dissolution, and agglomeration kinetics provided here can be readily combined with previously existing breakage/secondary nucleation models ,, for sodium chlorate to quantitatively simulate complex crystallization processes such as deracemization through Viedma ripening or temperature cycling. , …”
Section: Introductionmentioning
confidence: 99%